The impact of BASEL accords on the management of Vietnamese commercial banks - Hai Long Pham; Kevin James Daly (Journal of Risk and Financial Management, 2020)
This paper is an attempt to empirically examine the impact of Basel Accord regulatory guidelines on the risk-based capital adequacy regulation and bank risk management of Vietnamese commercial banks. Our research aims to assess how Vietnamese commercial banks manage their capital ratio and bank risk under the latest Basel Accord capital adequacy ratio requirements. Building on previous studies, this research uses a simultaneous equation modeling (SiEM) with three-stage least squares regression (3SLS) to analyze the endogenous relationship between risk-based capital adequacy standards and bank risk management. A year dummy variable (dy2013) is included in the model to take account of changes in the regulation of the Vietnamese banking system. Furthermore, we add a value-at-risk variable developed by as an independent variable into equations of the empirical models. The results reveal a significant impact of Basel capital adequacy regulatory pressure on the risk-based capital adequacy standards and bank risk management of Vietnamese commercial banks. Moreover, banks under the latest Basel capital adequacy regulations are induced to reduce risks and increase banks' financial performance.
Keywords: 330; risk management; Basel accords; risk-based capital adequacy requirement; simultaneous equation models (SiEM); three-stage least square (3SLS); Vietnamese commercial banks